The value of a law degree – part 3: a student perspective. Issue 4 (2nd October 2021) - Nicholson, Alex; Johnston, Paul
ABSTRACT: The "value" of university courses in the UK is increasingly equated with their potential for employability enhancement. Part 1 of this research utilized theory from the marketing discipline to highlight the many other aspects of value that a law degree in particular offers beyond lawyer qualification, and Part 2 presented a theory of value for the UK legal education market specifically, based upon the value propositions articulated by UK providers in their online prospectus pages. This third paper in the series explores student perspectives on this theme, identified through six life history interviews conducted with past and present LLB students from a post-92 university in the UK. The findings indicate that – whilst employability (and lawyer qualification specifically) is unquestionably important – there is still much untapped value potential that can be harnessed in order to differentiate law programmes in an increasingly competitive market. As the relevant regulatory body prepares to make radical changes to the way that solicitors qualify in England and Wales from 2021, the time for providers to develop differentiated and distinctive value is now.